Commentary concerning "measurement and correlation of solubility and solution thermodynamics of 1, 3-dimethylurea in different solvents from T = (288.15 to 328.15) K". (February 2019) - Xu, Renjie; Zheng, Min; Chen, Gaoquan; Chen, Jiao; Zhao, Hongkun
Highlights: Errors are found in the published equation coefficients for Wilson model. Published equation coefficients fail to describe the reported mole fraction solubility. The equation coefficients were re-regressed. Thermodynamic functions of mixing were re-calculated. Abstract: Errors were discovered regarding the published equation coefficients of Zhu and co-workers [J. Chem. Thermodynamics 97 (2016) 9–16] for mathematically describing the solubility behavior of 1, 3-dimethylurea in different pure solvents using the Wilson model. Larger differences were found between our back-calculated data and those reported in the authors' published paper. The expression of Wilson model was corrected and the equation parameters were re-regressed. In addition, the thermodynamic functions of mixing such as change of mixing Gibbs energy, mixing enthalpy and mixing entropy of mixing were re-calculated.